Female genital tuberculosis - Muñóz T., Carlos (2015)
We have found a high incidence of genital tuberculosis in the patients studied in the Infertility Clinic Hospital "Arzobispo Loayza". 1,080 infertile patients, 93 cases of genital tuberculosis is discovered; ie 8.6%. Of these 93 patients: 68 cases; ie 73.1% were sterile primary and 25 cases; ie 26.9%, sterile secondary. The incidence of genital tuberculosis in women who gather data from primary infertility and tubal obstruction, is very high. In our series, 30% of patients met this requirement, tuberculous endometritis was discovered. The prognosis of sick affected utero-adnexal tuberculosis and receive good medical treatment is relatively benign. The functional prognosis associated with the possibility of modifying infertility is still currently quite uncertain. Also, the prognosis regarding healing infection trompas- -the initial focus is less optimistic than it was thought at the beginning of the antibiotic era. In 42.1% of patients operated after treatment, we found persistent tubal histological injury. In the 93 patients studied in 10 years, we have managed three uterine pregnancies; ie 3.22%, from which 2 culminated in normal deliveries and the third was interrupted by a spontaneous abortion. Simultaneously, ectopic pregnancies found 6 corresponding to 6.45% of the 93 cases and 66.6% of all pregnancies.